Effect of metal-ceramic or all-ceramic superstructure materials on stress distribution in a single implant-supported prosthesis: Three-dimensional finite element analysis - Gomes, Érica Alves [UNESP]; Barão, Valentim Adelino Ricardo [UNESP]; Rocha, Eduardo Passos [UNESP]; De Almeida, Érika Oliveira [UNESP]; Assunção, Wirley Gonçalves [UNESP] (My University, 2011)
Purpose: This three-dimensional finite element analysis study evaluated the effect of different material combinations on stress distribution within metal-ceramic and all-ceramic single implant-supported prostheses. Materials and Methods: Three-dimensional finite element models reproducing a segment of the maxilla with a missing left first premolar were created. Five groups were established to represent different superstructure materials: GP, porcelain fused to gold alloy; GR, modified composite resin fused to gold alloy; TP, porcelain fused to titanium; TR, modified composite resin fused to titanium; and ZP, porcelain fused to zirconia. A 100-N vertical force was applied to the contact points of the crowns. All models were fixed in the superior region of bone tissue and in the mesial and distal faces of the maxilla section. Stress maps were generated by processing with finite element software. Results: Stress distribution and stress values of supporting bone were similar for the GP, GR, TP, and ZP models (1,574.3 MPa, 1,574.3 MPa, 1,574.3 MPa, and 1,574.2 MPa, respectively) and different for the TR model (1,838.3 MPa). The ZP model transferred less stress to the retention screw (785 MPa) than the other groups (939 MPa for GP, 961 MPa for GR, 1,010 MPa for TP, and 1,037 MPa for TR). Conclusion: The use of different materials to fabricate a superstructure for a single implant-supported prosthesis did not affect the stress distribution in the supporting bone. The retention screw received less stress when a combination of porcelain and zirconia was used. © 2011 by Quintessence Publishing Co Inc.
Keywords: Finite element analysis; Implant-supported dental prosthesis; Metal-ceramic alloys; Zirconium